Utilization of Moringa Leaf Extract in Processed Products Pudding as an Effort to Prevent Anemia - Febry Mutiariami Dahlan; Armanih; Febriana R; Rizqiyatun A; Yusniar Tito; Ati Herawati; Nurita Y; Septiani H (Rajaki of Tulip Medika Publisher, 2025)
Objective: This community service was carried out with the aim of overcoming priority problems at the Bekasi City Hospital, namely anemia in pregnant women. Method: The method used in this community service uses lectures, discussions, and demonstrations. The target is pregnant women who experience anemia. Results: The results of this community service, pregnant women understand and comprehend the counseling and complementary therapy